2021
DOI: 10.3390/children8090807
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Risk of School-Aged Children with Viral Infection among Diarrhea Clusters in Taiwan during 2011–2019

Abstract: Acute diarrhea is mainly caused by norovirus and rotavirus. Numerous factors modify the risk of diarrhea cluster infections and outbreaks. The purpose of this study was to explore the epidemiological characteristics, differences, and trends in the distribution of viral and bacterial pathogens that cause diarrhea cluster events as well as the public places where diarrhea cluster events took place in Taiwan from 2011 to 2019. We examined publicly available, annual summary data on 2865 diarrhea clusters confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sustained reduction of more than 30% was achieved versus the prevalence in the prevaccine period (27.8%; 2004-2006). The significantly increased NoV infection rates have replaced rotavirus as the leading cause of child hospitalizations for gastroenteritis [27,28,65,66]. In 2021, a study by Ballard et al [67] in the US showed that NoV is well-recognized as the leading cause of pediatric gastroenteritis in settings with universal rotavirus vaccination.…”
Section: Viral Gastroenteritis In Taiwan: From Rotavirus To Norovirusmentioning
confidence: 99%
“…Sustained reduction of more than 30% was achieved versus the prevalence in the prevaccine period (27.8%; 2004-2006). The significantly increased NoV infection rates have replaced rotavirus as the leading cause of child hospitalizations for gastroenteritis [27,28,65,66]. In 2021, a study by Ballard et al [67] in the US showed that NoV is well-recognized as the leading cause of pediatric gastroenteritis in settings with universal rotavirus vaccination.…”
Section: Viral Gastroenteritis In Taiwan: From Rotavirus To Norovirusmentioning
confidence: 99%
“…The authors are sure about the added value of this study that conforms with the public use of the government reports. [ 22 24 ]…”
Section: Methodsmentioning
confidence: 99%
“…The authors are sure about the added value of this study that conforms with the public use of the government reports. [22][23][24] 2.2. Definition of confirmed case and epidemiological survey [25] 2.2.1.…”
Section: Ethical Policymentioning
confidence: 99%
“…The data came from the Taiwan Centers for Disease and Control (TCDC), and it is public health surveillance rather than research that involved human subjects. Thus, institutional review board approval and informed consent were not required for these deidentified secondary data analyses [11][12][13].…”
Section: Ethical Policymentioning
confidence: 99%